2023
DOI: 10.7554/elife.86067
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytoneme structures and extracellular vesicles in Trichomonas vaginalis parasite-parasite communication

Abstract: Trichomonas vaginalis, the etiologic agent of the most common non-viral sexually transmitted infection worldwide, colonizes the human urogenital tract where it remains extracellular and adheres to epithelial cells. With an estimated annual prevalence of 276 million new cases, mixed infections with different parasite strains are expected. Although it is considered as obvious that parasites interact with their host to enhance their own survival and transmission, evidence of mixed infections call into question th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 101 publications
1
7
0
Order By: Relevance
“…In addition, it has been reported that cytonemes are associated with clump formation [34] and that highly adherent strains aggregate more than poorly adherent strains [18,34,35]. The authors demonstrated that different parasites inside the clumps are connected by cytonemes, which are longer filopodia extensions reaching up to ~300 nm from the originating cell body [34]. The authors reported that interaction between different strains induced cytoneme formation [36] and that parasite clumping is strain-dependent.…”
Section: Clumpingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported that cytonemes are associated with clump formation [34] and that highly adherent strains aggregate more than poorly adherent strains [18,34,35]. The authors demonstrated that different parasites inside the clumps are connected by cytonemes, which are longer filopodia extensions reaching up to ~300 nm from the originating cell body [34]. The authors reported that interaction between different strains induced cytoneme formation [36] and that parasite clumping is strain-dependent.…”
Section: Clumpingmentioning
confidence: 99%
“…One group [18] claimed that TvTSP8 from the Tetraspanin family (TvTSPs) was involved in parasite aggregation, suggesting a role for this protein in parasite interaction. In addition, it has been reported that cytonemes are associated with clump formation [34] and that highly adherent strains aggregate more than poorly adherent strains [18,34,35]. The authors demonstrated that different parasites inside the clumps are connected by cytonemes, which are longer filopodia extensions reaching up to ~300 nm from the originating cell body [34].…”
Section: Clumpingmentioning
confidence: 99%
“…falciparum (Khowawisetsut et al, 2023), Leishmania (Weber et al, 2023), T . cruzi (Cornet‐Gomez et al, 2023), Echinococcus multilocularis (Liu et al, 2023), and Giardia intestinalis (Salas et al, 2023), secrete EVs containing an assortment of bioactive molecules, including lipids, proteins, glycans, DNA, and RNA during infections (Chen et al, 2023; Gutierrez et al, 2022; Szempruch et al, 2016). These EVs serve as an efficient delivery system, transferring bioactive signals to target cells (Ofir‐Birin & Regev‐Rudzki, 2019; Szempruch et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…EVs play a critical role as mediators of intercellular communication in the interaction between parasites and their hosts or among parasites themselves (Mantel & Marti, 2014;Marcilla et al, 2014;Mardahl et al, 2019;Ofir-Birin et al, 2017). Multiple parasitic pathogens, such as P. falciparum (Khowawisetsut et al, 2023), Leishmania (Weber et al, 2023), T.cruzi (Cornet-Gomez et al, 2023), Echinococcus multilocularis (Liu et al, 2023), and Giardia intestinalis (Salas et al, 2023), secrete EVs containing an assortment of bioactive molecules, including lipids, proteins, glycans, DNA, and RNA during infections (Chen et al, 2023;Gutierrez et al, 2022;Szempruch et al, 2016). These EVs serve as an efficient delivery system, transferring bioactive signals to target cells (Ofir-Birin & Regev-Rudzki, 2019;Szempruch et al, 2016).…”
mentioning
confidence: 99%
“…Now, in eLife, Natalia de Miguel (Instituto Tecnológico Chascomús and Escuela de Bio y Nanotecnologías) and colleagues – including Nehuén Salas and Manuela Blasco Pedreros as joint first authors – report that different strains of the protozoan Trichomonas vaginalis , a parasite responsible for sexually-transmitted infections, communicate using extracellular vesicles and a type of filopodia called a cytoneme ( Salas et al, 2023 ). Cytonemes are thin specialized filopodia that can traffic signalling proteins ( Roy and Kornberg, 2015 ).…”
mentioning
confidence: 99%